Study of the morphologo-anatomic signs of shoots of the Salix caprea L. of Ukrainian flora - Borodina, Natalia; Kovalyov, Volodimir; Koshovyi, Oleh; Gamulya, Olga (ScienceRise: Pharmaceutical Science, 2019)
Representatives of the Salicaceae family are valuable sources of medicinal plant material that has long been used in traditional medicine in many countries around the world. In European countries, some willow species are official plants. The bark of young branches of different willow species, including Salix purpurea L., Salix fragilis L., Salix daphnoides Vill., have been included in the edition of the European Pharmacopoeia and since 2014 to the State Pharmacopoeia of Ukraine. Expanding the raw material base of medicinal plant raw materials is an urgent problem that can be solved through the introduction into the pharmaceutical practice of systematically close autochthonous and introduced willow species widespread in Ukraine. Aim. Determination of macro- and microscopic diagnostic features of the willow goat (Salix caprea L.) shoots growing in Ukraine, for the development of further regulatory documentation for medicinal plant raw materials and the use of standardized raw materials in the design of medicinal products based on willow shoots. Methods of the research. The object of the study were dry shoots of Salix caprea L. Vegetable raw materials were collected in May-August 2016-2018 in Kharkiv, Zakarpattia and Kiev region of Ukraine. Study of the morphological and anatomical structure of goat willow shoots was performed using the methods of light and electron microscopy. The ultrastructure of the epidermal leaf tissue surface was further studied using scanning microscopy techniques. Results of the research. An in-depth study of the morphological and anatomical structure of the shoots of Salix caprea L. has been carried out and the main diagnostic macro- and microscopic features of perspective medicinal raw materials have been established. Conclusions. The obtained results significantly expand information on the anatomical structure of shoots of Salix caprea L. flora of Ukraine and will be used in the standardization of raw materials of species of the family Willow